RESPON PERTUMBUHAN DAN PRODUKSI TANAMAN KUBIS BUNGA (Brassica oleracea L.) PADA BERBAGAI TAKARAN PUPUK TRICHOKOMPOS ASAL LIMBAH RUMEN SAPI - Novriani, Novriani; Aguzaen, Hendra (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2016)
Plant cauliflower (Brassica oleracea. L) is a plant which benefit as vegetables. Growth a nd yield of cauliflower can be enhanced by use of fertilizer Thichokompos origin cow rumen. The research aimed to explore the origin of the waste fertilizer Thichokompos origin cow rumen that can increase growth and yield of cauliflower. This research was conducted at trial garden Agriculture Faculty Baturaja University on April to July 2015. This research using Complete Randomised Design Non Factorial with 7 (seven) treatmen that 3 (tree) replication, in order to get 21 units of treatment. Based on the result of the research, the treatmen of sewage fertilizer Thichokompos origin cow rumen significantly affect the total weight matter, root fresh weight, shoot dry weight, root dry weight, root number, diameter and wet weight cauliflower. While at the variable height plant, the total number and the time which appnorgear influential (30 tons/ha) + Â½ dose of anorganic fertilizer was recommended as the best treatment which improve the growth of 63,75 % ad 116,15 % if compared to the control.